Thermo-physical properties of molten Cd-Ga alloys - RP Koirala; BP Singh; D Adhikari (Bibechana, 2013)
We report thermodynamic, microscopic and surface properties of Cd-Ga alloys in molten state at 700 K. We use quasi-chemical approximation for the computation of thermodynamic and microscopic properties. For the computation of surface we use Butler’s approach and quas-chemical approach. We also calculate the surface concentration of the individual component.